Optimal Size of Government in Turkey - Taner Turan (International Journal of Economics and Financial Issues, 2014)
This paper examines the relationship between a size of the government and the economic growth and estimates the optimal size of the government for Turkey by using two different specifications. We find that the optimal size of the central government varies from 8.8 (15.4) to 9.1 (17) percent of GDP for 1950-2012 (1970-2012) period, depending on the specification. The optimal size of the central government expenditures excluding the interest payments is 14.4 percent of GDP. The actual rates have been well above the estimated optimal ones for a long time. The results of our quadratic specification also suggest that Armey curve is valid for Turkey during the period examined. We find that the estimated optimal sizes of the government from different specifications are consistent with each other, but there is a substantial variation in the size when different time periods are used. This shows that Armey curve is sensitive to change in the time periods. Our results clearly point out that the Turkish government should cut its expenditures in order to have a growth maximizing size.